Effects of Carbohydrates Supplementation and Physical Exercise: A Review - R., Roscamp; G., Santos M. (Challenges in Disease and Health Research Vol. 7, 2021)
Carbohydrates are the most abundant biomolecules on Earth. They are important for muscle contraction during prolonged exercise performing at moderate intensity and short duration exercise performed at high-intensity [1,2]. There is a considerable amount of studies related to the ergogenic effects of nutritional resources in sport performance [3]. Carbohydrates are important for muscle contraction during performance of prolonged exercise at moderate intensity and high-intensity exercise with short duration. Based on this evidence, this article aims to review the physiological and biochemical concepts and definitions of carbohydrates; searches for a relation between the consumption of carbohydrates and daily studies; and mainly analyzes the relations between consumption of carbohydrates and physical performance, analogously before, during and after the competition. To conduct the study was first done a widespread research looking for articles and scientific studies, and after that the research was filtered using up-to-date articles. The power of an athlete directly influences his physical performance [4]. In the pre-competition stage stored glycogen increases and prevents from depletion [5]. Supplementation during competition aims to replenish lost fluids and carbohydrates [6]. After a competition it is necessary to rehydrate, fill glycogen stores and recreate an electrolyte balance [3]. Literature reviews are important connectors that have been studied….. where the science must advance. More research should be done to get to know the ideal carbohydrate intake appropriate for each sport.